Testing for latitudinal gradients in defense at the macroevolutionary scale. (5th September 2018) - Anstett, Daniel N.; Ahern, Jeffrey R.; Johnson, Marc T.J.; Salminen, Juha‐Pekka
Abstract: Plant defenses against herbivores are predicted to evolve to be greater in warmer climates, such as lower latitudes where herbivore pressure is also thought to be higher. Instead, recent findings are often inconsistent with this expectation, suggesting alternative hypotheses are needed. We tested for latitudinal gradients in plant defense evolution at the macroevolutionary scale by characterizing plant chemical defenses across 80 species of the evening primroses, spanning both North and South America. We quantified phenolics in leaves, flowers, and fruits, using advanced analytical chemistry techniques. Dominant individual ellagitannin compounds, total concentrations of ellagitannins, flavonoids, total phenolics, and compound diversity were quantified. Variation in these compounds was predicted with latitude, temperature, precipitation, and continent using phylogenetic generalized least squares (PGLS) multiple regression models. Latitude did not strongly explain variation in chemical defenses. Instead, fruit total ellagitannins, oenothein A, and total phenolics were greater in species inhabiting regions with colder climates. Using analytical chemistry and 80 species in two continents, we show that contrary to classic predictions, concentrations of secondary metabolites are not greater at lower latitudes or in warmer regions. We propose higher herbivore pressure in colder climates and gradients in resource availability as potential drivers of the observed patterns in Oenothera.